2022
DOI: 10.1111/ijlh.13787
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory characterization of obligate carriers of type 3 von Willebrand disease with a potential role for Platelet Function Analyzer (PFA‐200)

Abstract: Introduction Type 3 von Willebrand disease (VWD) is a rare autosomal recessive disorder characterized by undetectable von Willebrand Antigen (VWF:Ag). Carriers of type 3 VWD carry one null allele and have von Willebrand factor (VWF) at about 50% of normal. The aim of this study was to characterize type 3 VWD carriers and to study the role of Platelet Function Analyzer (PFA‐200) in this cohort. Methods This was a cross‐sectional study where data were collected from carriers (parents/offspring) of type 3 VWD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…43,52 Normal PFA-100 results are especially rare in patients with abnormal VWF function or a lower quantity of large molecular VWF multimers. 24,26,32,35,60,78,80,81 In cases of mild type 1 VWD the false-negative rate is higher. Sap et al reported a sensitivity of only 29%, specifically in this group of patients.…”
Section: Results Of the Point-of-care Tests In Patients With Heredita...mentioning
confidence: 99%
See 1 more Smart Citation
“…43,52 Normal PFA-100 results are especially rare in patients with abnormal VWF function or a lower quantity of large molecular VWF multimers. 24,26,32,35,60,78,80,81 In cases of mild type 1 VWD the false-negative rate is higher. Sap et al reported a sensitivity of only 29%, specifically in this group of patients.…”
Section: Results Of the Point-of-care Tests In Patients With Heredita...mentioning
confidence: 99%
“…PFA-100 is extensively studied in patients with (suspected) VWD. 17 18 19 21 22 23 24 26 27 28 29 30 31 32 33 34 35 36 37 43 51 52 53 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 Favaloro et al reported an overall sensitivity of 83.2% and 91.5% of the ADP and EPI cartridge respectively in a review in 2008. 79 A current analysis including all articles published before and after 2008 yielded similar test performance outcomes, as shown in Fig.…”
Section: Results Of the Point-of-care Tests In Patients With Heredita...mentioning
confidence: 99%
“…For comparison, some CT NRRs reported in the contemporary 6,16–29 and original literature 30–53 are shown in Figure 3. In most instances, these NRRs differ from each other and also from the manufacturer ranges, especially for C/ADP.…”
Section: Resultsmentioning
confidence: 99%
“…The Siemens product information CT NRRs are shown by the green horizontal dashed lines. Figure A shows NRRs from some contemporary literature as obtained from the recent literature search (see Methods), and reflecting information from the past 3 years 6,16–29 . Figure B shows NRRs from some early literature as otherwise reviewed in Reference 10 30–53 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation